Strategi manajemen risiko operasional pada bank syariah di era digital - Frasasti, Meilinda (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has brought about major changes in the banking world, including for Islamic banks. On the one hand, digitalization opens up great opportunities for efficiency and ease of service. However, on the other hand, it also presents new challenges in the form of increasingly complex operational risks from cyber threats to potential system errors that can impact customer trust. This article discusses the importance of an operational risk management strategy that is not only responsive to technological developments but also adheres to sharia principles. In its discussion, various strategic approaches are outlined, such as strengthening IT infrastructure, ongoing HR training, synergy between technology divisions and sharia supervisors, and the preparation of a sharia-based risk assessment framework. In closing, this article recommends that Islamic banks build an adaptive and ethical risk management system, involve sharia supervision in every stage of digital innovation, and continue to educate all parties regarding the importance of maintaining trust in the digital era. That way, Islamic banks can maintain stability, trust, and blessings in carrying out their functions amidst the rapid flow of technological transformation.